2022
DOI: 10.3389/fpsyt.2021.770353
|View full text |Cite
|
Sign up to set email alerts
|

Brain Connectivity and Symptom Changes After Transcranial Magnetic Stimulation in Patients With Borderline Personality Disorder

Abstract: ObjectivesRepetitive transcranial magnetic stimulation (rTMS) is an innovative method in the treatment of borderline personality disorder (BPD). We hypothesized that prefrontal rTMS in patients with BPD leads to improved BPD symptoms and that these effects are associated with brain connectivity changes.MethodsFourteen patients with BPD received 15 sessions of individually navigated prefrontal rTMS over the right dorsolateral prefrontal cortex. Clinical effects were measured by the Borderline Symptom List 23, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Using an adapted version of a functional magnetic resonance imaging emotion regulation task, Cremers et al [22] found that BPD participants displayed higher amygdala connectivity strength compared to healthy controls (HC) in their exploratory analyses. When investigating the effects of transcranial magnetic stimulation on BPD participants, Sverak et al [23] observed significant decreases in amygdala and insula connectivity following treatment, which correlated with symptom reduction. In their study using random forest models based on clinical and neuroimaging data to predict the response to dialectical behavior therapy (DBT), Schmitgen et al [24] also identified amygdala-and parahippocampus-activation during a cognitive reappraisal task as central regions related to dysfunctional emotion regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Using an adapted version of a functional magnetic resonance imaging emotion regulation task, Cremers et al [22] found that BPD participants displayed higher amygdala connectivity strength compared to healthy controls (HC) in their exploratory analyses. When investigating the effects of transcranial magnetic stimulation on BPD participants, Sverak et al [23] observed significant decreases in amygdala and insula connectivity following treatment, which correlated with symptom reduction. In their study using random forest models based on clinical and neuroimaging data to predict the response to dialectical behavior therapy (DBT), Schmitgen et al [24] also identified amygdala-and parahippocampus-activation during a cognitive reappraisal task as central regions related to dysfunctional emotion regulation.…”
Section: Resultsmentioning
confidence: 99%
“…Uma das abordagens inovadoras que está ganhando destaque é o uso de técnicas de neurofeedback e estimulação magnética transcraniana (EMT) como terapias adjuvantes no TPB (Konstantinou et al, 2021). O neurofeedback envolve o treinamento do cérebro para autoregular padrões de atividade cerebral específicos, enquanto a EMT utiliza campos magnéticos para modular a atividade neuronal em regiões específicas do cérebro (SVERAK et al, 2022). Estudos preliminares sugerem que essas técnicas podem ser eficazes na redução de sintomas do TPB, como impulsividade e instabilidade emocional, oferecendo novas opções de tratamento para os pacientes (Sverak et al, 2022).…”
Section: Perspectivas Futuras No Tratamento Do Tpbunclassified
“…In MDD and PTSD patients, 5 Hz TMS to the dlPFC was also found to reduce the problematic hyperconnectivity between the sgACC, the insula and the DMN ( Philip et al, 2018 ). In borderline personality disorder, HF-rTMS over the right dlPFC yielded a decrease in connections between the amygdala/insula and precuneus, PCC, and parietal lobules ( Sverak et al, 2021 ). Similarly, tDCS over the left dlPFC led to increased long-term cerebral blood flow to the ACC ( Jog et al, 2021 ), and reduced activation of the amygdala ( Ironside et al, 2019 ).…”
Section: Neuroscience-informed Interventions: Brain Stimulationmentioning
confidence: 99%